Integrating usability engineering and agile software development: A literature review - Sohaib, O; Khan, K (2010 International Conference On Computer Design and Applications, 2010)
The various agile software development methodologies have promoted since their inception and even demanded high degree to improve the quality of the software product. Usability engineering has made its way into the software mainstream and has caught the attention of software engineers and researchers worldwide due to rapidly growing and volatile internet software industry, despite their different perspectives on creating software both have a major role in making good software. Usability focuses on how the end users will work with the software and agile development focuses on how the software should be developed. The way these two perspectives are being combined in practice is still not well understood. This study is a preliminary literature review that describes the key question that how usability-engineering practices should be integrated with agile software development in order to make stronger and effective usable software system. This paper focuses on identifying the tensions between usability and agile methods. The research aim is to identify the common approach of agile methods and usability engineering by surveying extensive related work on integration of usability and agile methods.